Business Semantic Management and Data Governance Programs and Their Impact on Financial Reporting Systems and Corporate Financial Performance - Vojvodic, Milomir; Špička, Jindřich, 1981-; Štrach, Pavel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This research investigates the economics of data, levels, and aspects of utilized benefits associated with their economic potential in the data economy, levels and aspects of their efficient control for compliance purposes - considering the new regulatory framework of European Union and General Data Protection Regulation (EU GDPR). Compliance costs are significant and data related regulations are more frequent. The study argues if compliance spending then can also generate additional value, as just a minimal regulation requirements fulfillment is not by any means achieving a competitive advantage. The value is narrowed to the fields of innovation and operational efficiency in this exploration driven quantitative research. Rather than in technological, the aim of the project is to look in governance and leadership related organizational practices for empirical proof, where multiple predictor, mediator, and moderating variables were measured in order to offer a range of potential managerial interventions. To test the hypotheses, a quantitative method with Structural Equation Modelling and Partial Least Squares (PLS) in SmartPLS tool is used. The empirical data is collected from 98 data management professionals involved in recent GDRP projects associated with party data in larger organizations across Europe. The study proves that Data Governance Span (DGS) leads to the increase of both data compliance related variables - Data Compliance Innovation (DCI) and Privacy Project Efficiency (PPE) - at the same time. However, its effect on the increase of Data Compliance Innovation (DCI) is weaker than the effect on the increase of Privacy Project Efficiency (PPE). Customer-Centric Orientation (CCO) is discovered to be an underlying mechanism of the relationship Data Governance Span (DGS) - Data Compliance Innovation (DCI).
Governance Teal Leadership (GTL) leads to the increase of both Data Governance Span subconstructs at the same time: Cross-Functional Integration (CFI) and Line-of-Business Stakeholders Participation (LOBSP), and this effect is stronger on the former subconstruct.
Vedoucí práce: Jindřich Špička
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations